2005
DOI: 10.4049/jimmunol.174.4.2318
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of S100A8 by Glucocorticoids

Abstract: S100A8 (A8) has roles in inflammation, differentiation and development and is associated with oxidative defense. Murine A8 (mA8) is up-regulated in macrophages, fibroblasts, and microvascular endothelial cells by LPS. Glucocorticoids (GCs) amplified LPS-induced mA8 in these cells. Relative to stimulation by LPS, GCs increased mA8 gene transcription and mRNA half-life. Enhancement required new protein synthesis, IL-10 and products of the cyclooxygenase-2 pathway, and both ERK1/2 and p38 MAPK. Protein kinase A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 61 publications
10
100
0
1
Order By: Relevance
“…Known as the endogenous Toll-like receptor 4 agonist (20), S100A8 has been shown to be regulated by glucocorticoids upon LPS stimulation (21). In our study, we found that transcriptional activation of HIF-1 in myeloid cells regulates S100A8 (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Known as the endogenous Toll-like receptor 4 agonist (20), S100A8 has been shown to be regulated by glucocorticoids upon LPS stimulation (21). In our study, we found that transcriptional activation of HIF-1 in myeloid cells regulates S100A8 (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Stability of the S100A7 mRNA and protein are unknown but may be a factor in this persistence. The closely related S100A8 gene shows an mRNA half life of B8 h that can be increased up to 20 h by glucocorticoid treatment (Hsu et al, 2005). Similarly, S100A4 mRNA and protein half life has been shown to be B8 h and B85 h, respectively (Rivard et al, 2007).…”
Section: Inflammatory Cytokines Induce S100a7 Expression In Breast Cellsmentioning
confidence: 99%
“…Medium and mediators were only used if endotoxin levels were Ͻ20 pg/ml (chromogenic Limulus amebocyte assay; Associates of Cape Cod) (4,29). Bovine calf serum (HyClone) had been pretested before purchase.…”
Section: Monocyte and Macrophage Preparationmentioning
confidence: 99%
“…Human monocytes isolated from peripheral blood of healthy subjects as previously described (29) were analyzed using a Beckman Coulter counter. Preparations generally contained ϳ10% monocytes, ϳ90% lymphocytes, and Ͻ1.5% granulocytes.…”
Section: Monocyte and Macrophage Preparationmentioning
confidence: 99%
See 1 more Smart Citation